An improved modulation method for matrix converters with unbalanced output loading - Ali, S.; Wolfs, Peter (2014)
© 2014 ACPE. In this paper Instantaneous Reactive Power (IRP) theory is applied to develop an improved modulation method for Matrix Converters (MCs) operating with unbalanced loads. IRP theory shows that, for unbalanced loading conditions, the instantaneous power contains a constant component and a component that fluctuates at twice the fundamental frequency. In conventional modulation schemes the power fluctuation results in input current harmonics. The new method removes the harmonic distortion by synthesizing an input current vector that contains positive and negative sequence components that satisfy the power balance requirements but have only fundamental frequency components. The paper shows that the conventional modulation method may be converted to produce the required input current vector by phase modulation of the input current vector.